Parallel communicating Watson-Crick automata systems - Czeizler, Elena; Czeizler, Eugen (Acta Cybernetica, 2006)
Watson-Crick automata are finite state automata working on doublestranded tapes, introduced to investigate the potential of DNA molecules for computing. In this paper we introduce the concept of parallel communicating Watson-Crick automata systems. It consists of several Watson-Crick finite automata parsing independently the same input and exchanging information on request, by communicating states to each other. We investigate the computational power of these systems and prove that they are more powerful than classical Watson-Crick finite automata, but still accepting at most context-sensitive languages. Moreover, if the complementarity relation is injective, then we obtain that this inclusion is strict. For the general case, we also give some closure properties, as well as a characterization of recursively enumerable languages based on these systems.